2020
DOI: 10.3389/fmicb.2020.573829
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Plasticity of the Transcriptome Under Temperature Fluctuations in the Fungal Plant Pathogen Zymoseptoria tritici

Abstract: Most species live in a variable environment in nature. Yet understanding the evolutionary processes underlying molecular adaptation to fluctuations remains a challenge. In this study we investigate the transcriptome of the fungal wheat pathogen Zymoseptoria tritici after experimental evolution under stable or fluctuating temperature, by comparing ancestral and evolved populations simultaneously. We found that temperature regimes could have a large and pervasive effect on the transcriptome evolution, with as mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…These findings extend observations from previous studies illustrating parallel transcriptome adaptation after imposition of a uniform selection pressure. Under laboratory conditions, convergence towards a shared genic transcriptome has been observed several times in bacteria [ 49 52 ] and even in fungi [ 53 ]. One study of P .…”
Section: Discussionmentioning
confidence: 99%
“…These findings extend observations from previous studies illustrating parallel transcriptome adaptation after imposition of a uniform selection pressure. Under laboratory conditions, convergence towards a shared genic transcriptome has been observed several times in bacteria [ 49 52 ] and even in fungi [ 53 ]. One study of P .…”
Section: Discussionmentioning
confidence: 99%
“…These findings extend observations from previous studies illustrating parallel transcriptome adaptation after imposition of a uniform selection pressure. Under laboratory conditions, convergence towards a shared genic transcriptome has been observed several times in bacteria (47)(48)(49)(50) and even in fungus (51). One study of P. aeruginosa transcriptomes from an explanted lung showed that genetically distinct strains exhibited minimal variability in their transcriptomes (52),…”
Section: How Do Transcriptomes Evolve?mentioning
confidence: 99%
“…Because the expression of genes affect phenotypic traits, and thus condition the individual fitness, gene expression levels are believed to be driven by natural selection, at least for a subset of genes. For instance, specific sets of genes have been shown to evolve in a direction consistent with prior knowledge in the wild (Philippe et al, 2007;Verta and Jones, 2019;Huang et al, 2021), or during experimental evolution (Philippe et al, 2007;Ghalambor et al, 2015;Jallet et al, 2020). In contrast, the structure of the network itself is less directly subject to natural selection.…”
Section: Introductionmentioning
confidence: 99%